ESTIMATED GENETIC INDEXES FOR BODY WEIGHT IN LAMAS - García V., Wilber (2007)
Parturition, weaning and shearing data of K´aras and Ch´accus lamas, collected from 1995 to 2001 at the IVITA Research Center, Maranganí of San Marcos University, was used in the present study to estimate the heritability (h2), repeatability and genetic correlations between body weight at birth, weaning and first and second shearing, by adjusting the fata for the effect of year, age of mother and sex of baby lama. The h2 value was analyzed by the nested effect using a model for brothers, brothers in law and by regression baby-mother. Heritability for body weight for both K´aras and Ch´accus lamas was high, while for birth weight and weight at first and second shearing varied from medium to high. The repeatability estimated by intraclass correlation for body weight of Ch´accus and K´aras was lower (0.3-0.4) than those estimated by regression (0.6-0.7, respectively). Genetic correlations between body weight at birth and at weaning and first shearing, and between body weight at weaning and at first shearing wee high and positive in both strains. These estimations are reliable to choose the appropriate selection index method for a genetic improvement program in lama meat production.